Ant Communities Resist Even in Small and Isolated Gypsum Habitat Remnants in a Mediterranean Agroecosystem - Azcárate, Francisco M.; Alameda-Martín, Aitor; Escudero, Adrián; Sánchez, Ana M. (Frontiers in Ecology and Evolution, 2021)
Natural and seminatural habitat remnants play a crucial ecological role in intensified agroecosystems. However, some controversy persists on the conservation value of small and poorly connected fragments in a hostile matrix. In addition, oncoming paradigm on the value of these remnants comes from generalization obtained from reduced group of organisms (mostly plants and vertebrates). To date, few studies have analyzed the effect of fragmentation on ant communities in Mediterranean agroecosystems, despite the importance of this group of animals on several key ecosystem functions and services. Here, we analyze the effects of fragment area and connectivity on ant communities in gypsum outcrops in a large cereal agroecosystem of Central Spain. Ant communities were described by their species composition, abundance (total number of occurrences), and number of species, standardized both by area (species density) and abundance (species richness). Observed number of species was relatively high in comparison with other studies in the Mediterranean, and we found no effects of fragment characteristics on species density, species richness and species composition, which implies that small and isolated patches do not present any change in their ant conservation value. Moreover, total number of occurrences tended to increase for small fragments. This finding contrasts with the results reported for other groups in similar gypsum habitats and suggests that certain ant traits and strategies make them particularly resistant to fragmentation and capable to take advantage of small habitat patches. Given the important ecological role played by ants, we recommend the preservation of these small habitat fragments in the management plans of agroecosystems in these drylands, especially in those cases in which intensification of agricultural practices greatly diminish natural habitat availability.